2011
DOI: 10.3102/0034654311423382
|View full text |Cite
|
Sign up to set email alerts
|

Science Teacher Learning Progressions

Abstract: Learning progressions are the successively more sophisticated ways of thinking about an idea that follow one another over a broad span of time. This review examines the research on science teachers’ pedagogical content knowledge (PCK) in order to refine ideas about science teacher learning progressions and how to support them. Research published between 1986 and 2010 relevant to science teacher learning and PCK was examined for what ways teachers’ knowledge becomes more developed and what appears to be the seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(89 citation statements)
references
References 72 publications
3
66
0
4
Order By: Relevance
“…Several authors have further defined and elaborated on PCK (Abell, 2008;Loughran, Mulhall, & Berry, 2008;Park & Oliver, 2008;Schneider & Plasman, 2011;Van Driel, Verloop, & De Vos, 1998). Changing to a context-based curriculum requires teachers to change their practices and beliefs, not just with respect to materials, pedagogies and assessment, but even with respect to purposes and goals of science teaching and beliefs about science teaching and learning.…”
Section: Teacher Learningmentioning
confidence: 99%
“…Several authors have further defined and elaborated on PCK (Abell, 2008;Loughran, Mulhall, & Berry, 2008;Park & Oliver, 2008;Schneider & Plasman, 2011;Van Driel, Verloop, & De Vos, 1998). Changing to a context-based curriculum requires teachers to change their practices and beliefs, not just with respect to materials, pedagogies and assessment, but even with respect to purposes and goals of science teaching and beliefs about science teaching and learning.…”
Section: Teacher Learningmentioning
confidence: 99%
“…A solid CK background is an essential condition, but it is not a sufficient condition for teaching science effectively in elementary schools (Oh & Kim, 2013). Schneider and Plasman (2011) suggested that understanding students' prior conceptions is the first step for developing science teachers' learning progression of PCK, but several studies indicated teachers are insensitive to students' prior conceptions as a critical constructivist component of knowledge about learners (Lin, 2016b;Lin & Chiu, 2010;Chi, Siler, & Jeong, 2004;Liang, Chou, & Chiu, 2011). Research on one-to-one tutoring has found that tutors predicted students' conceptions based on their own personal learning experiences, overestimated the accuracy of students' conceptions, and had difficulty monitoring their students' conceptions (Chi et al, 2004;Herppich, Wittwer, Nückles, & Renkl, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous studies have pointed out that it is a challenge for teachers to transform their CK and PK into PCK and to enact it into practices (van Driel & Berry, 2012). Although there is no consensus about the components of PCK models (Kind, 2009), Schneider and Plasman (2011) suggested that science teachers' learning progression of PCK starts from considering students' thinking about science (e.g., students' prior knowledge, initial science ideas, previous experiences). Van Driel, Berry, and Meirink (2014) stated that "At the heart of PCK lies what teachers know about how their students learn specific subject matter or topics and the difficulties or misconceptions students may have regarding this topic" (p. 849).…”
Section: Introductionmentioning
confidence: 99%
“…Son numerosas las progresiones de aprendizaje que aparecen en la literatura con relación al aprendizaje de contenidos de ciencias, pero son menos en relación con el conocimiento didáctico del contenido en ciencias, a pesar de que se entienden como de gran importancia para la formación de profesores (Schneider y Plasman, 2011;Talanquer, 2014). Nuestro estudio pretende aportar resultados en este campo, identificando niveles de aprendizaje de maestros en formación inicial acerca de la presentación de los contenidos para los alumnos, la utilización didáctica de sus ideas, la secuenciación de actividades y la finalidad de la evaluación, a partir de la primera y última versión de un diseño para enseñar ciencias elaborado por los participantes en el curso desarrollado.…”
unclassified